Possibility study of implementing vertical constructed wetland for domestic waste water treatment in urban kampong - Haryati Sutanto; Paulus Bawole (Jurnal Teknosains, 2021)
The Indonesian Ministry of Environment in 2014 released study results that 60-70% of rivers in Indonesia have been polluted by domestic wastewater, which is not treated properly. Improper and inadequate wastewater treatment not only pollutes water resources and damages ecosystems, but can also pose a significant public health risk. The development of spontaneous settlements in urban kampong makes the environmental quality within the settlements getting worse and many people consider that the area of urban kampong is not habitable. The efforts to treat wastewater before being discharged into water bodies are very important. The study of "vertical constructed wetland" model using water plants which are also ornamental plants can be considered as an alternative system for household wastewater treatment in kampong settlements.  The objective of the research is to develop an alternative model of wastewater treatment that can overcome the obstacles of implementing a wastewater treatment system in terms of cost and availability land. The result shows that the removal efficiency of BOD, phosphate and total coliform are 71.64%, 50,92% and 99.67% respectively. Since the research is still being conducted on a laboratory scale, the further study must be developed with real case studies in low income community settlements in Kampung Kota. Additionally this research can give suggestions to local government an alternative policy to implement domestic waste water treatment plan in a densely populated settlement along the riverbank in the city.